Animal models and hypoxia : proceedings of an International Symposium on Animal Models and Hypoxia, held at Wiesbaden, Federal Republic of Germany, 19 November 1979 - Stefanovich, V. (Pergamon Press, 1981)
Animal Models and Hypoxia consists of proceedings from an international symposium. The text discusses the developments made on the study of brain metabolism. An article about the regional utilization of glucose in the brain of mammals is presented. There is also a section that reviews the energy metabolism in the nervous system of insects. The topics covered includes the role of sympathetic innervation in the regulation of cerebral blood flow during hypercapnia, the comparative aspects of energy metabolism in non-mammalian brains under normoxic and hypoxic conditions, and an anoxic rat model.